Implikasi Hukum Kesalahan Dalam Salinan Akta Notaris Terhadap Keautentikan Akta Asli - Derizky, Reyno Iksan; Purwanto, I Wayan Novy (Acta Comitas; Vol 10 No 01 (2025)DO - 10.24843/AC.2025.v10.i01.p11, 2025)
The goal of this research is to assess the legal ramifications of an error or mistake in the copy of the notarial deed against the authenticity of the original deed. The focus of this research lies in the impact of those mistakes or errors in the copy against the evidentiary power of the authentic deed and notary's legal responsibilities regulated in Article 51 of Regulations Number 2 of 2014 and Articles 1870 and 1365 of the Civil Code of the Republic of Indonesia. This research employed a normative legal approach through literature studies, focussing on the analysis of legal products and relevant literature. The results of the study show that although errors or mistakes in the copy do not affect the validity of the original deed, they can reduce the status of the copy of the deed from an authentic notarial deed to a private deed, so that its evidentiary power is reduced. These mistakes or errors can also result in legal liability for the Notary, both administratively and civilly, especially if it is proven to cause losses to the related parties. This research underscores the significance of precision in the draughting and replication of deeds, particularly notarial deeds, and highlights the necessity for enhanced oversight of the notary profession to mitigate the potential for mistakes or errors. There are some improvement efforts, such as through official record or addendums, must be carried out in accordance with legal provisions in order to maintain the integrity of the legal document.